Antiretroviral therapy adherence and predictors to adherence in Albania: a cross-sectional study - Shane Douglas Morrison; Vania Rashidi; Clea Sarnquist; Vilson H Banushi; Michael K Hole; Namrata J Barbhaiya; Valbona H Gashi; Lars Osterberg; Yvonne Maldonado; Arjan Harxhi (Journal of Infection in Developing Countries)
Introduction: The possibility of an HIV/AIDS epidemic in southeastern Europe (SEE) is not improbable. Thus, an understanding of the current issues surrounding HIV/AIDS care, specifically antiretroviral therapy (ART) adherence, in countries within SEE is critical. This study was conducted to determine the ART adherence characteristics of Albania’s HIV-positive population. Methodology: This cross-sectional study reports initial demographic and adherence characteristics of patients receiving HIV/AIDS treatment in Albania. Retrospective review of pharmacy medications dispensed supplemented reported adherence behavior. Further, an adherence index was utilized to explore adherence more thoroughly. Results: Patient-reported adherence and pharmacy review showed adherence levels of 98.9±4.4% and 97.7±4.7%, respectively. Assessment by adherence index revealed an index level of 91.7±6.7. Factors associated with a score of < 95 on the adherence index were: being partnered (OR = 0.29, 95% CI = 0.09 – 0.98), history of depression (OR = 0.24, 95% CI = 0.08 – 0.76), increased number of barriers to care (OR = 0.80, 95% CI = 0.66 – 0.97), and increased number of current social and medical needs (OR = 0.72, 95% CI = 0.58 – 0.91). Conclusions: Interventions aimed at reducing barriers to care, addressing current medical and social needs, and treating mental health issues may help improve adherence to ART in patients with HIV/AIDS in Albania. With little known about HIV/AIDS in SEE, this study provides guidance on how SEE countries can help prevent a possible rise in the prevalence of HIV given the close link of ART adherence and spread of HIV.